Teaching and listening and speaking in second and foreign language contexts - Bailey, Kathleen M. (London, England : Zed Books, 2020)
"This book guides language teachers in planning and teaching activities that promote the development of speaking and listening skills at all levels of target language proficiency, for teachers of any modern language. Kathleen M. Bailey draws on her extensive experience as a language teacher, teacher educator, and language learner to interweave practical activities with the research and theory that support their use. Activities include the use of pictures, songs, drama techniques, tasks, and projects to promote the development of speaking and listening skills. The author shares reflections of her own and encourages readers to reflect on their own experiences and become aware of their existing mental constructs through multiple reflection tasks and discussion questions. Each chapter provides focusing questions. The systematic chapter structure scaffolds the readers' understanding of the concepts explored, which include communication strategies, interactive and non-interactive listening, speaking anxiety, accentedness and intelligibility, and much more. Through its companion website this book provides access to resources that enable readers to continue their own professional development as teachers of listening and speaking in second and foreign language contexts."--
Acknowledgements 1. Teaching Speaking and Listening: An Introduction 2. Teaching Speaking and Listening through the Ages 3. Language Proficiency and Communicative Competence 4. Second Language Acquisition and Teaching Speaking and Listening 5. Teaching Listening in a Second or Foreign Language 6. Teaching Speaking in a Second or Foreign Language 7. Teaching Interactive Speaking and Listening 8. Tasks and Projects in Teaching Listening and Speaking 9. Speaking and Listening Fluency 10. Teaching Pronunciation in a Second or Foreign Language 11. Pragmatics, Speech Events, and Speech Acts -- 12. Assessing L2 Listening 13. Assessing L2 Speaking 14. Assessing Interactive Speaking and Listening -- References Index
Includes bibliographical references (pages 205-213) and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Second language acquisition -- Study and teaching; Language and languages -- Study and teaching -- Audio-visual aids; Speech; Teachers' classroom resources & material; Electronic books